Impact of TP53 mutations in breast cancer: Clinicopathological features and prognosisImpact of TP53 mutations in breast CA. Issue 7 (15th May 2020) - Li, Xuerui; Chen, Xiaoqing; Wen, Lingzhu; Wang, Yulei; Chen, Bo; Xue, Yunlian; Guo, Liping; Liao, Ning
Abstract: Background: TP53 is a crucial tumor suppressor gene. However, the mutation pattern of TP53 in Chinese patients with breast cancer has not yet been determined. Methods: A total of 411 untreated patients with invasive breast cancer diagnosed at Guangdong Provincial People's Hospital (GDPH) between June 2017 to September 2018 were recruited into the study. Mutational alterations in TP53 were detected and correlations between TP53 mutations and clinicopathological features analyzed. Comparative analysis of the data in the GDPH cohort with those in the METABRIC cohort were carried out. Results: A significantly higher rate of TP53 mutations was detected in the GDPH cohort (51.3%) compared with the METABRIC cohort (34.4%) ( P < 0.01). In the GDPH cohort, 77.8% of the mutations were located in the conserved areas across exons 5–8 of TP53 ; among these, 112 were identified as missense mutations and mainly clustered in the DNA‐binding region. R273C/H ( n = 11) and R248Q/W ( n = 10) were two of the most common mutation sites of TP53 detected in the cohort of GDPH patients. Logistic regression multivariate analysis showed that histological grade III, ki‐67 > = 25%, HR‐ and Her2+ in breast cancer had higher mutation probability of TP53 ( P < 0.001 in the GDPH cohort). Furthermore, receiver operating characteristic (ROC) model combining molecular typing and Ki‐67 was established to predict the mutation of TP53, and the AUC was 0.846. Conclusions: A significantly higher rate of TP53 mutation was detected in the Chinese cohort compared with the METABRIC. Correlation analysis revealed a significant association of TP53 mutation with HR‐ and HER2+, higher Ki‐67 and histological grade in breast cancer patients.